Lung extracellular matrix modulates KRT5+ basal cell activity in pulmonary fibrosis - Richard J. Hewitt; Franz Puttur; David C. A. Gaboriau; Frédéric Fercoq; Maryline Fresquet; William J. Traves; Laura L. Yates; Simone A. Walker; Philip L. Molyneaux; Samuel V. Kemp; Andrew G. Nicholson; Alexandra Rice; et al. (Nature Communications, 2023)
Abstract Aberrant expansion of KRT5+ basal cells in the distal lung accompanies progressive alveolar epithelial cell loss and tissue remodelling during fibrogenesis in idiopathic pulmonary fibrosis (IPF). The mechanisms determining activity of KRT5+ cells in IPF have not been delineated. Here, we reveal a potential mechanism by which KRT5+ cells migrate within the fibrotic lung, navigating regional differences in collagen topography. In vitro, KRT5+ cell migratory characteristics and expression of remodelling genes are modulated by extracellular matrix (ECM) composition and organisation. Mass spectrometry- based proteomics revealed compositional differences in ECM components secreted by primary human lung fibroblasts (HLF) from IPF patients compared to controls. Over-expression of ECM glycoprotein, Secreted Protein Acidic and Cysteine Rich (SPARC) in the IPF HLF matrix restricts KRT5+ cell migration in vitro. Together, our findings demonstrate how changes to the ECM in IPF directly influence KRT5+ cell behaviour and function contributing to remodelling events in the fibrotic niche.